MEDICAL ETHICS: PERCEPTION AND PRACTICE - K. K .Mah; J. K. Candlish (Asian Journal of Medicine & Health Sciences, 2019)
Medicolegal cases continue to rise despite the establishment of medical ethics as a core component in the undergraduate medical education. This study sought to discover how senior medical students perceive medical ethics when they assume the roles respectively of doctor, patient and an immediate relative when facing ethical dilemmas. It also sought to discover the extent to which religion, cultural factors and their perceived severity of illnesses affects their judgements. Using multiple choice questionnaires, students were found to have assimilated universal ethical principles well, but paradoxically most students in the second phase of the enquiry, indicated that religion, cultural sensitivities and severity of illness will have a great influence on their decisions after they graduate.